Gastrointestinal Toxicities in Women During Breast Cancer Chemotherapy Treatment - Kameo, Simone Yuriko (2021)
Introduction: Chemotherapeutic agents for breast cancer treatment often cause systemic toxicities in patients, including gastrointestinal alterations. Objective: To identify gastrointestinal toxicities in women during breast cancer chemotherapy. Method: Descriptive-exploratory, quantitative and cross-sectional study using medical records of patients undergoing chemotherapy between February 2014 and February 2015 in an oncology service. After screening and selection, 194 patients were included. Results: In general, 457 gastrointestinal clinical manifestations were identified, of which 50.5% of the participants had up to two and 49.5% had between three and five. In addition, 74.2% had nausea, 43.3% abdominal pain, 40.7% diarrhea, 39.2% vomiting and 37.6% constipation. The occurrence of three to five toxicities was related to the occurrence of fatigue (p=0.002) and weight loss (p=0.003), as well as the number of chemotherapy cycles positively influenced the severity of nausea (p=0.041) and vomiting (p=0.023). The chemotherapeutic agents taken did not influence the occurrence of these toxicities. Lastly, nausea and vomiting (p<0.001), as well as abdominal pain and diarrhea (p=0.003) occurred. Conclusion: Clinical manifestations of gastrointestinal toxicity associated with chemotherapy were frequent in women with breast cancer. The simultaneous occurrence of these manifestations may be associated with fatigue and weight loss, as well as severity may be associated with the number of chemotherapy cycles.